Effect of environmental and behavioural factors on microbiological air quality of operating rooms - Singh, Gurmail; Biswal, Manisha; Koushal, Vipin; Dhaliwal, Navneet (International Journal of Infection Control, 2022)
Introduction: An operating theatre (OT) is a very complex setup, which presents numerous challenges for both patients and health care providers. A safe OT environment decreases the susceptibility of patients to postoperative infections. Therefore, a study was conducted to determine microbiological air quality for establishing baseline values and to assess concurrently the effect of environment and behavioural factors in 46 OTs of a tertiary care hospital. Materials & Methods: The OTs were divided into two groups based on the type of air flow: laminar diffuser (Group I) or conventional diffuser (Group II). Two hundred and thirty-eight samples were collected with an active technique using a sieve impactor, sampling at 100 L/minute. Statistical analysis was conducted using Statistical Package for Social Sciences (SPSS) Version 20 (IBM Corp., Armonk, NY). Results: In Group I OTs with the laminar diffuser, bacterial and fungal values during the lean period for environmental and behavioural factors were 47.78 colony forming units (CFM)/m3 and 0.24 CFU/m3, respectively. The bacterial and fungal values during the surgical period were 98.01 CFU/m3 and 0.40 CFU/m3, respectively. The same values for Group II OTs with the conventional diffuser were 52.83 CFU/m3 and 0.39 CFU/m3 during the lean period, and 80.06 CFU/m3 and 0.40 CFU/m3 during the surgical period. Discussion: Both environmental and behavioural factors – temperature, humidity, percentage of fresh air in circulation, door type, controlled entry, minimal door opening and proper OT attire – were seen to contribute concurrently to maintaining air quality in operating units.